Bed of roses [compact disc, unabridged] - Roberts, Nora (Roberts, Nora. Bride quartet, 2009)
Since she was a little girl, Emma Grant has always loved romance. So it's really no surprise that she has found her calling as a wedding florist. She gets to play with flowers every day and work with her three best friends in the process. She couldn't ask for a better job, and on the surface, Emma's love life seems to be thriving.